The mind's evaluation - Abdul Aziz, Nor Akmar; Marzuki, Mohd Jamaluddin; Mohamed Mokhtar, Mohamed Daniel; Mohd Saad, Mohamad Ridzuan (Universiti Putra Malaysia Press, 2016)
Plants, water, air and other nature elements embedded in a forest of an urban green space give a different mind evaluation or perception. Generally, each socio-demographic group shares different thoughts and views on green area. Their interpretation varies according to their assumption, knowledge, exposure and experience.